2021
DOI: 10.3390/ijms22042053
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Stress Response of Near-Isogenic Spring Durum Wheat Lines under Different Sowing Densities

Abstract: A detailed study was made of changes in the plant development, morphology, physiology and yield biology of near-isogenic lines of spring durum wheat sown in the field with different plant densities in two consecutive years (2013–2014). An analysis was made of the drought tolerance of isogenic lines selected for yield QTLs (QYld.idw-2B and QYld.idw-3B), and the presence of QTL effects was examined in spring sowings. Comparisons were made of the traits of the isogenic pairs QYld.idw-3B++ and QYld.idw-3B−− both w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Especially in the case of wheat, the effects of water shortage depend on onset time, duration and intensity. Aside from the developmental stages and the severity of the stress, the effects of water shortage on cereals depend on soil type, environmental conditions [30,31], the cultivated varieties or species [32,33] and also the cultivation technologies employed [34,35]. Drought can cut wheat yields by up to 92% [27], but sometimes extreme drought at the right time can lead to a total yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the case of wheat, the effects of water shortage depend on onset time, duration and intensity. Aside from the developmental stages and the severity of the stress, the effects of water shortage on cereals depend on soil type, environmental conditions [30,31], the cultivated varieties or species [32,33] and also the cultivation technologies employed [34,35]. Drought can cut wheat yields by up to 92% [27], but sometimes extreme drought at the right time can lead to a total yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the multiplicity of factors influencing field experiments, these studies provided, in some cases, contrasting results with each other and compared to controlled-environment studies. In this regard, Bányai et al [ 45 ] evaluated the antioxidant response under rain-fed and well-watered conditions in the flag leaf at the flowering stage of eight near-isogenic lines of spring durum wheat, selected for yield QTLs. Authors reported a significant increase (on average) of POX activity in the non-irrigated treatment compared to irrigated plots, while a decrease of APX activity was observed, resulting of a similar order of magnitude for all the isogenic lines (averaging about 70%) [ 45 ].…”
Section: Effect Of Hyperosmotic Stress On Antioxidant Defence System In Durum Wheatmentioning
confidence: 99%
“…In this regard, Bányai et al [ 45 ] evaluated the antioxidant response under rain-fed and well-watered conditions in the flag leaf at the flowering stage of eight near-isogenic lines of spring durum wheat, selected for yield QTLs. Authors reported a significant increase (on average) of POX activity in the non-irrigated treatment compared to irrigated plots, while a decrease of APX activity was observed, resulting of a similar order of magnitude for all the isogenic lines (averaging about 70%) [ 45 ]. Interestingly, APX activity was in significant positive correlation with the number of spikelets on the main spike ( r = 0.803***), and POX activity with the number of sterile basal spikelets ( r = 0.847***) [ 45 ].…”
Section: Effect Of Hyperosmotic Stress On Antioxidant Defence System In Durum Wheatmentioning
confidence: 99%
“…Quantitative trait loci (QTLs) are the nucleotides sequence on the genome controlling the trait of interest. It requires the progenies/population developed from crosses between desirable parents which includes RILs (recombinant inbred lines), backcross progenies, F 2 population, double haploid and near isogenic lines ( Kim et al, 2021a , Kim et al, 2021b , Bányai et al, 2021 ). QTL mapping have advantages viz., rare allele identification, few genetic markers requirement and no population structure effects.…”
Section: Introductionmentioning
confidence: 99%
“…QTL mapping have advantages viz., rare allele identification, few genetic markers requirement and no population structure effects. Whereas, disadvantages includes long period to develop populations, costly, laborious, limited detection of QTLs and few events of recombination consequently coarse mapping ( Kim et al, 2021a , Kim et al, 2021b , Bányai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%